Neuroprotective Activity of Hypericum perforatum and Its Major Components - Oliveira, Ana I.; Pinho, Cláudia; Sarmento, Bruno; Dias, Alberto C. P. (Frontiers in Plant Science, 2016)
Hypericum perforatum is a perennial plant, with worldwide distribution, commonly known as St. John’s wort. It has been used for centuries in traditional medicine for the treatment of several disorders, such as minor burns, anxiety and mild to moderate depression. In the past years, its antidepressant properties have been extensively studied. Despite that, other H. perforatum biological activities, as its neuroprotective properties have also been evaluated. The present review aims to provide a comprehensive summary of the main biologically active compounds of H. perforatum, as for its chemistry, pharmacological activities, drug interactions and adverse reactions and gather scattered information about its neuroprotective abilities. As for this, it has been demonstrated that H. perforatum extracts and several of its major molecular components have the ability to protect against toxic insults, either directly, through neuroprotective mechanisms, or indirectly, through is antioxidant properties. H. perforatum has therefore the potential to become an effective neuroprotective therapeutic agent, despite further studies that need to be carried out.